Sobański’s Critique of the (Particular) Legislation - Kroczek, Piotr (Philosophy and Canon Law, 2022)
Legislation is an art. Fr. Professor Remigiusz Sobański, who analyzed the particular legislation of the (Arch)diocese of Katowice in his scientific activity, was very well aware of this. These academic analyses allowed him to draw up numerous observations and comments, as well as postulates with regard to this law. This article focuses on the formal aspects of law addressed by the great canonist.